Effectiveness of a prevention program in mental health by socratic dialogue and critical thinking (2016)
Objective: The purpose of this study was to analyze the impact of the prevention program by Socratic dialogue and critical thinking, on depression and anxiety. Method: Participants were 110 students who entered their freshman year; an experimental design with experimental and control group was used. Independent variable was Socratic dialogue and critical thinking, and dependent variables were depression and/or anxiety symptoms, and negative, positives and anxious thoughts. Applied instruments consisted on Center for Epidemiologic Studies Depression Scale (CES-D), Symptom Check List - 90 Revised (SCL-90R), Automatic Thoughts Questionnaire - Revised (ATQ-RP), and Anxious Self-Statements Scale (ASSQ). Results: By comparisons between the two groups, it was observed the effectiveness of the program in negative thought reduction, although no other effects were identified. Conclusions: Socratic dialogue and critical thinking can - like a prevention program, negative thoughts change in students at freshman year. © 2016, Universidad del Norte. All rights reserved.